Assessment of Low Back Pain: Reliability and Minimal Detectable Change of the Brief Pain Inventory. - Song, Chen-Yi; Chen, Chia-Hsin; Chen, Tien-Wen; Chiang, Hsin-Yu; Hsieh, Ching-Lin (American Journal of Occupational Therapy)
Importance: The Brief Pain Inventory (BPI) is one of the most widely used measures to assess pain and related impacts among patients with low back pain (LBP). However, its test–retest reliability and minimal detectable change (MDC) have rarely been examined in patients with LBP, interfering with its utility. Objective: To investigate the test–retest reliability and MDC of the BPI among patients with LBP. Design: Repeated assessments design with a 1-wk interval. Setting: Department of Physical Medicine and Rehabilitation in a hospital in Taiwan. Participants: Fifty-four patients with stable LBP conditions. Outcomes and Measures: The BPI has two subscales—Intensity and Interference—that assess pain intensity and pain interference, respectively. Their test–retest reliability was examined using the intraclass correlation coefficient (ICC), and MDCs were calculated. Results: The ICCs of the Intensity and Interference subscales were.62 and.76, respectively. The MDC values for the two subscales were 2.57 and 2.34, respectively. For the four Intensity items, the average-pain score had a higher ICC (.60) than scores on the other items (worst, least, and current pain, which had ICCs of about.40). Conclusions and Relevance: The results suggest that although the BPI is a commonly used measure of pain intensity and pain interference among patients with LBP, caution should be exercised in interpreting the Intensity subscale score and its item scores. What This Article Adds: The BPI is widely used to assess pain and related impacts on daily occupation and functioning among patients with LBP. This study provides information regarding its test–retest reliability. Moreover, the MDC values provide clinicians and researchers with the thresholds for determining real improvement (beyond random measurement error). Although the Brief Pain Inventory is a commonly used pain intensity and pain interference measure for patients with low back pain, this study suggests that caution should be exercised in interpreting the Intensity subscale score and its item scores.